Biomimicry: a Necessary Eco-Ethical Dimension for a Future Human Sustainability - Javier Collado-Ruano (International Society of Philosophy and Cosmology, 2015)
This article reflects on the concept of "global citizenship" from a transdisciplinary methodology and a biomimetic approach. A sustainable human image appears with this epistemological symbiosis, that constitutes the DNA of a genuine tool of civilizational transformation. On the one hand, the transdisciplinary methodology is opened to the multi-referential conception of the three pillars proposed by Basarab Nicolescu (2008): levels of reality, logic of the included middle, and complexity. On the other hand, the concept of biomimicry approached by Janine M. Benyus (2012) identifies nine operating principles of life in order to mimic nature in the reformulation of new sustainable human production systems with the biosphere. The aim of this study is to identify international agreements on environmental and sustainable development, to elaborate some contribution in the post-2015 eco-political-educational strategic framework led by the United Nations with the Sustainable Development Goals. With the purpose of strengthening ties between education and sustainability through symbiotic bridges between nature and culture, the work identifies the vital axises that constitute the interdependence of ecosystems to make a biomimetic application in the social, political, and educational structures of human systems. Then, this paper is an innovational research that seeks to integrate the eco-ethics as a practice in the "Global Citizenship Education" proposed for UNESCO for next decade 2015-2025.